2014
DOI: 10.1002/2013ja019516
|View full text |Cite
|
Sign up to set email alerts
|

The plasma depletion layer in Saturn's magnetosheath

Abstract: A plasma depletion layer (PDL) of reduced plasma density and enhanced magnetic field strength can form in the magnetosheath (shocked solar wind) adjacent to the magnetopause boundary of a planetary magnetosphere. The dominant factor controlling the level of plasma depletion and field enhancement in Earth's PDL is the magnetic shear across the magnetopause, due to the influence of this parameter on magnetic reconnection at the boundary. Here we examine the PDL in Saturn's magnetosheath using Cassini spacecraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
(105 reference statements)
1
18
0
Order By: Relevance
“…This leaves 262 crossings where we have the magnetic field vector and electron number density in both the adjacent magnetosheath and magnetosphere. Note that the captured conditions in the magnetosheath are affected by the presence of a plasma depletion layer, and those in the magnetosphere are affected by the presence of a low‐latitude boundary layer (e.g., Figure ) [ Masters et al ., , ]. Conditions on both sides of Saturn's magnetopause are highly variable, and our statistics capture the level of this variability.…”
Section: Cassini Observations At Saturn's Magnetopausementioning
confidence: 99%
See 2 more Smart Citations
“…This leaves 262 crossings where we have the magnetic field vector and electron number density in both the adjacent magnetosheath and magnetosphere. Note that the captured conditions in the magnetosheath are affected by the presence of a plasma depletion layer, and those in the magnetosphere are affected by the presence of a low‐latitude boundary layer (e.g., Figure ) [ Masters et al ., , ]. Conditions on both sides of Saturn's magnetopause are highly variable, and our statistics capture the level of this variability.…”
Section: Cassini Observations At Saturn's Magnetopausementioning
confidence: 99%
“…This is most likely because the local magnetosheath magnetic field strength (which primarily controls the electric field strength) is similarly not guaranteed to be relatively high when the system is compressed (see supporting information). We suggest that this is due to magnetosheath variability, particularly the presence of mirror mode structures that can significantly reduce the local magnetic field strength [ Violante et al ., ; Masters et al ., ].…”
Section: The Reconnection Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…By testing its validity, this will also provide additional means in approximating the magnetic field in a region where Cassini is 128 not present to make observations. The magnetosheath during these four traversals was measured to have relatively steady IMF orientations throughout the traversal, also used in the work by Masters et al [2014]. This one-to-one approach is not suitable with the MHD simulation since the grid size near the magnetopause and bow shock is ~0.5 R s .…”
Section: Correspondence Between Observations and Predictive Modelmentioning
confidence: 99%
“…Gershman et al (2013) also reported a large-scale PDL often forming just exterior of Mercury's subsolar magnetopause as a result of piled-up draped magnetic flux around the magnetosphere. This has been attributed to the low av- Masters et al (2014), on the other hand, show no PDL response to cross-magnetopause magnetic shear because the magnetic flux transport rates associated with reconnection are too low to have any effect. Nonetheless, it is expected that the IMF orientation strongly controls where reconnection is occurring because of the β-imposed constraint of close to anti-parallel fields required for reconnection onset [Masters et al, 2012].…”
Section: Introductionmentioning
confidence: 99%